The TRANSFORMATIONAL LEADERSHIP STYLE RELATIONS AND ORGANIZATIONAL CULTURE WITH EMPLOYEE WORK SATISFACTION PT. INDOMARCO PRISMATAMA - Situmorang, Deby Friska; Anggraen, Nenny i (Fundamental Management Journal, 2018)
labor is one of the important factors that must be considered by the company, both leaders and employees who are determinants in order to the a achieve company goals. This leadership style is basically a transformational leadership style that a leaders creating a vision and environment that motivates subordinates a expectations. besides that it takes organizational culture that is an employees to act, think, and solve problems so as to guide them in working. This research is descriptive correlational with a sample of 40 people and analysis data using Spearman rank analysis. Keywords: transformational leadership, organizational culture, job satisfaction